The Impact of The Jurisprudential Analytical Inquiry Learning Model Assisted by Augmented Reality (Assemblr Edu) on Critical Thinking Abilities in Biology For 10th Grade High School Students - Oktafiani, Raicha; Haka, Nukhbatul Bidayati; Roniawati (Lembaga KITA, 2024)
The study is in the background with learners' low critical thinking ability in learners' activities. In the learning process, instead of using a media learning model, it can also be used as an aid. One of the learning models and the media is Jurisprudential Analytical Inquiry assisted Augmented Reality Assembly Edu. This study intends to identify the learning model Jurisprudential Analytical Inquiry assisted Augmented Reality Assembly Edu to the critical operation of class X Biology subjects at SMA. This research is a quantitative study using the Quasy Experiment Method. The research population was taken using 2 X MIPA classes, and the research sample consisted of X MIPA 6 as the Experiment class and X MIPA 3 as the Control class, with a total of 68 students. The sample technique in this study is the Cluster Random Sampling Technique. The research test instrument used multiple choice questions and tested the hypothesis using an independent t-test. Data was obtained from the results of hypothesis calculations using independent sig value tests. (2-tailed) that is 0.00 less than 0.05. So it can be concluded that the hypothesis in this study is accepted, meaning that there is an influence of the learning model Jurisprudential Analytical Inquiry assisted Augmented Reality Assembly Edu to the critical operating of class X Biology subjects at SMA.